La réception territoriale du changement climatique ou comment le changement climatique contribue à l’émergence de territoires et de politiques climatiques spécifiques - Florence Rudolf (VertigO, 2012)
The climate change gradually takes place in our lives through narratives, which incite action. Policies for mitigation and climate change adaptation are the main response actually developed by governments. They appeal to different skills. First ones stage a risk and incite to prevent it ; the seconds give evidence of what the announced changes are well and truly present. If the policies for adaptation are on the agenda, which contents should we give them ? We have started to investigate this question on the city scale, in France.